2013
DOI: 10.1093/mmy/myt003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Alternaria infectoria extracellular vesicles

Abstract: Many fungi use membrane vesicles to transport complex molecules across their cell walls. Like mammalian exosomes, fungal vesicles contain lipids, proteins, and polysaccharides, many of which are associated with virulence. Here we identify and characterize extracellular vesicles (EVs) in Alternaria infectoria, a ubiquitous, environmental filamentous fungus that is also an opportunistic human pathogen. Examination of the A. infectoria EVs revealed a morphology similar to that of vesicles described in other funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 42 publications
6
70
1
Order By: Relevance
“…Like for those previously described in C. neoformans and other fungal species, we found a large functional distribution of identified hits (23)(24)(25)(26)(27). The distribution carried through all the size-enriched populations, suggesting that any loading mechanism is size independent.…”
Section: Discussionsupporting
confidence: 84%
“…Like for those previously described in C. neoformans and other fungal species, we found a large functional distribution of identified hits (23)(24)(25)(26)(27). The distribution carried through all the size-enriched populations, suggesting that any loading mechanism is size independent.…”
Section: Discussionsupporting
confidence: 84%
“…Fungal EVs contain a complex combination of macromolecules, including many proteins, neutral lipids, glycans and pigments347910141518. This complex molecular mixture, including many cytoplasmic components, is consistent with the proposed origin of fungal EVs as cytoplasmic subtractions19.…”
supporting
confidence: 68%
“…Fungal cells are encased within a dense cell wall, so mechanisms are required for the transport of molecules across the wall for extracellular release in these organisms. In recent years, a number of studies have shown that the trafficking of molecules across the fungal cell wall requires extracellular vesicles (EVs)3456789101112131415161718.…”
mentioning
confidence: 99%
“…The first filamentous fungus from which EVs were isolated was Alternaria infectoria , a ubiquitous environmental fungus that spoils food crops and causes pulmonary infections in humans. Morphologically, the A. infectoria EVs resemble EVs from yeast species and are enriched with proteins that function in polysaccharide metabolism and DNA repair …”
Section: Filamentous Fungimentioning
confidence: 99%